Magnetic breakdown and angle-dependent magnetoresistance oscillations - Blundell, S; Nowojewski, A; Goddard, P (2010)
We describe how the presence of magnetic breakdown affects the appearance of angle-dependent magnetoresistance oscillations in an organic metal. The model takes account of all the contributions from quasiparticles undergoing both magnetic breakdown and Bragg reflection at each junction and allows extremely efficient simulation of data which can be compared with experimental results on κ-(BEDT-TTF) 2Cu(NCS) 2. © 2010 Elsevier B.V. All rights reserved.